2013
DOI: 10.1103/physrevb.88.134508
|View full text |Cite
|
Sign up to set email alerts
|

Impurity-induced subgap bound states in alkali-doped iron chalcogenide superconductors

Abstract: Measurements of the local density of states near impurities can be useful for identifying the superconducting gap structure in alkali doped iron chalcogenide superconductors KxFe2−ySe2. Here, we study the effects of nonmagnetic and magnetic impurities within a nearest neighbor d-wave and next-nearest neighbor s-wave superconducting state. For both repulsive and attractive nonmagnetic impurities, it is shown that sub-gap bound states exist only for d-wave superconductors with the positions of these bound states… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Within experimental resolution, the peak was found to remain centered at zero bias as a function of both STM tip position and application of c-axis applied magnetic fields up to 8 T. Furthermore, it was measured to extend uniformly in space with a length scale of order 3-4 Å, and decrease in amplitude (but not split) when proximate to other impurity bound states [361]. These peculiar properties are not characteristics of standard in-gap bound states of FeSCs arising from magnetic or nonmagnetic impurities [393][394][395][396][397]. Intriguingly, similar robust zero-energy conductance peaks have been recently detected near Fe adatoms, deposited on top of the stoichiometric materials LiFeAs and PbTaSe 2 [398], and on monolayers of FeSe/STO and FeTe 0.5 Se 0.5 /STO [399].…”
Section: Experimental Evidence For Majorana Zero Modes: Defect Statesmentioning
confidence: 98%
“…Within experimental resolution, the peak was found to remain centered at zero bias as a function of both STM tip position and application of c-axis applied magnetic fields up to 8 T. Furthermore, it was measured to extend uniformly in space with a length scale of order 3-4 Å, and decrease in amplitude (but not split) when proximate to other impurity bound states [361]. These peculiar properties are not characteristics of standard in-gap bound states of FeSCs arising from magnetic or nonmagnetic impurities [393][394][395][396][397]. Intriguingly, similar robust zero-energy conductance peaks have been recently detected near Fe adatoms, deposited on top of the stoichiometric materials LiFeAs and PbTaSe 2 [398], and on monolayers of FeSe/STO and FeTe 0.5 Se 0.5 /STO [399].…”
Section: Experimental Evidence For Majorana Zero Modes: Defect Statesmentioning
confidence: 98%
“…However, for phase-changing pairing symmetries such as d-wave and s±-wave, it is predicted that non-magnetic impurities with proper scattering potentials, can also induce in-gap states and suppress superconductivity [43][44][45], which is supported by STM measurements on cuprates [28], NaFeAs [32] and LiFeAs [46]. Meanwhile, several theoretical works have shown that non-magnetic impurities can also help to identify the pairing symmetry of KxFe2-ySe2 [47][48][49], which has similar band structure with (Li0.8Fe0.2)OHFeSe.…”
Section: F Impurity Effectmentioning
confidence: 99%
“…Besides the non-d-wave [e.g., extended s ± -wave (31)] pairing possibility of the 1-UC FeSe/SrTiO 3 (001), the scattering from the Fe adatom inducing the ZEBS here is not at the unitary limit in statistics (section S1). Recent theoretical advances have extended the magnetic impurity states to iron-based superconductors treated as spin-singlet pairing with both sign-preserving (s ++ -wave) and sign-reversing (s ± -wave; nodal and nodeless d-wave) SC-gap functions over the Fermi surfaces (32)(33)(34). In these models, the impurity-state energy can be tuned to zero for a critical strength of the scattering potential (32,34), which appears in agreement with the detected ZEBS and demands more experiments to scrutinize the ZEBS identity.…”
Section: Scrutiny Over Nontopological Physicsmentioning
confidence: 99%
“…Recent theoretical advances have extended the magnetic impurity states to iron-based superconductors treated as spin-singlet pairing with both sign-preserving (s ++ -wave) and sign-reversing (s ± -wave; nodal and nodeless d-wave) SC-gap functions over the Fermi surfaces (32)(33)(34). In these models, the impurity-state energy can be tuned to zero for a critical strength of the scattering potential (32,34), which appears in agreement with the detected ZEBS and demands more experiments to scrutinize the ZEBS identity. Physically, the impurity state is doubly degenerate at zero energy with both spin-up and spin-down components (29), which will be split by an applied magnetic field.…”
Section: Scrutiny Over Nontopological Physicsmentioning
confidence: 99%